Influence of perfluorinated ionomer in PEDOT:PSS on the rectification and degradation of organic photovoltaic cells. Issue 33 (6th August 2018) - Howells, Calvyn T.; Saylan, Sueda; Kim, Haeri; Marbou, Khalid; Aoyama, Tetsua; Nakao, Aiko; Uchiyama, Masanobu; Samuel, Ifor D. W.; Kim, Dong-Wook; Dahlem, Marcus S.; André, Pascal
Abstract : Fluorinated additives in PEDOT:PSS slow organic solar cell degradation and the underlying mechanisms and potentials are discussed. Abstract : Poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) is widely used to build optoelectronic devices. However, as a hygroscopic water-based acidic material, it brings major concerns for stability and degradation, resulting in an intense effort to replace it in organic photovoltaic (OPV) devices. In this work, we focus on the perfluorinated ionomer (PFI) polymeric additive to PEDOT:PSS. We demonstrate that it can reduce the relative amplitude of OPV device burn-in, and find two distinct regimes of influence. At low concentrations there is a subtle effect on wetting and work function, for instance, with a detrimental impact on the device characteristics, and above a threshold it changes the electronic and device properties. The abrupt threshold in the conducting polymer occurs for PFI concentrations greater than or equal to the PSS concentration and was revealed by monitoring variations in transmission, topography, work-function, wettability and OPV device characteristics. Below this PFI concentration threshold, the power conversion efficiency (PCE) of OPVs based on poly(3-hexylthiophene-2, 5-diyl):[6, 6]-phenyl-C61 -butyric acid methyl ester (P3HT:PCBM) are impaired largely by low fill-factors due to poor charge extraction. Above the PFI concentration threshold, we recover the PCE before it is improved beyond the pristine PEDOT:PSS layer based OPV devices. Supplementary to the performance enhancement, PFI improves OPV device stability and lifetime. Our degradation study leads to the conclusion that PFI prevents water from diffusing to and from the hygroscopic PEDOT:PSS layer, which slows down the deterioration of the PEDOT:PSS layer and the aluminum electrode. These findings reveal mechanisms and opportunities that should be taken into consideration when developing components to inhibit OPV degradation.